Potential Pedagogical Benefits and Limitations of Multimedia Integrated Desktop Video Conferencing Technology for Synchronous Learning - Schols, Maurice (International Journal of Advanced Corporate Learning (iJAC), 2009)
As multimedia gradually becomes more and more an integrated part of video conferencing systems, the use of multimedia integrated desktop video conferencing technology (MIDVCT) will open up new educational possibilities for synchronous learning. However, the possibilities and limitations of this technology must be clearly understood so that it can be used to maximize possible pedagogical benefits and reduce possible pedagogical limitations. This paper analyses the process of integrating MIDVCT in a first-year English language course, and offers insights into theoretical underpinnings of multimedia learning from two perspectives: the generative theory of multimedia learning and the cognitive overload theory. The data discussed in this paper have been drawn from a study which took place in a cross institutional setting at Fontys University of Applied Sciences, The Netherlands. The data were collected and analyzed according to a qualitative approach.